EXTRACT OF Sargassum echinocarpum ALLEVIATES OXIDATIVE STRESS IN STREPTOZOTOCIN-INDUCED DIABETIC RATS - Muhamad Firdaus (Universitas Gadjah Mada, 2011)
Oxidative stress occured in streptozotocin-induced diabetic rats. The ability of Sargassum echinocarpum to ameliorate the oxidative stress after treatment with streptozotocin was investigated in rats. Adult male rats were intraperitoneally injected with 45 mg/kg of streptozotocin to produce experimental oxidative stress characteristic of diabetes mellitus. Hyperglycemia was observed in blood serum after 10 days of streptozotocin treatment. There were a significant decrease in the activity of superoxide dismutase (SOD), catalase (CAT) and glutathione peroxide (GPx) and a significant increase in the levels of malondialdehyde (MDA) in the serum of diabetic rats. It indicated that there were an increasing lipid peroxidation and oxidative stress in the diabetic rats. Providing S. echinocarpum extract for 90 days on diabetic rats significantly improved the oxidative stress evidenced by a decreasing of MDA serum level and an increasing SOD, CAT and GPx activities than streptozotocin-treated rats. These results showed that the extract might improve the clinical manifestation of diabetes mellitus and decrease the oxidative stress in the diabetic rats. This effects appear to be due to its antioxidant properties.